KORELASI PENGETAHUAN KESEHATAN GIGI DAN MULUT DENGAN JARINGAN PERIODONTAL PADA PENDERITA DIABETES MELITUS - Lies Elina; Desi Andriyani; Erni Gultom; Yenny Lisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Background: Diabetes in the oral cavity, collectively referred to as “oral diabetes,” can cause tooth decay, dryness in the mouth, calculus buildup, gums that bleed easily (also called gingivitis), gingivitis itself, and alveolar resorption. Linkage Between Diseases: There is an increase in gum problems among diabetes sufferers reaching 72% because public awareness about dental and oral health has decreased in recent years. Purpose of the study: To determine the correlation between dental and oral health knowledge and periodontal tissue in diabetes mellitus sufferers. Methods: Type of analytical descriptive research with Chi-square design. Results:Data analysis used the chi-square test. The results of the chi-square statistical test showed that there was no correlation between dental and oral health knowledge and periodontal tissue in diabetes mellitus sufferers with a P value of 0.405 (> 0.05). This means there is no correlation. Conclusion: There is no correlation between knowledge of dental and oral health and periodontal tissue of diabetes mellitus sufferers at the Way Halim II Health Center in Bandar Lampung.